School Disruption: A Good Excuse for Teacher Reflections - Vásquez Villanueva, Salomón (2019)
The aim of this research is to catalog the predictive factors, consequences and solutions of school disruption, in the context of school coexistence and student learning. To achieve this goal, several investigations on school disruption have been addressed concerning to their conceptions, their predictive factors, disruptive behaviors, consequences, solutions and theories. In conclusion, the prevention and solution of disruptive behaviors are very important. In this sense, a deep and reflective analysis must be carried out on the contexts, the predictive factors and the consequences; also interpret disruptive behaviors correctly, creating an environment of communication and coexistence, according to theories and systemic approaches.